The Role of Islamic Boarding Schools as Educational Institutions for Forming the Character of Students - Siswanto, Heru; Muhammad, Aliyu Dahiru (Anjasmoro: Islamic Interdisciplinary Journal, 2024)
Islamic boarding schools are Islamic educational institutions that provide teaching, education, and example every second, minute, and hour from a kyai to its students. Education in Islamic boarding schools aims to forge students into independent individuals and develop a spirit of togetherness, which includes an attitude of mutual assistance, solidarity, and brotherhood among fellow students. In terms of individual character development, Islamic boarding schools teach a frugal attitude and simple living that is far from consumerism. The role of Islamic boarding schools in Indonesia is not only as educational institutions but also as religious institutions which are the basis for the process of forming the character of the people. In Islamic boarding schools, the basics of science are taught to shape the character of the people, because having good character is an obligation that students must have when they enter society. As a da'wah mission in the form of providing an example. Thus, Islamic boarding schools as Islamic educational institutions have great potential for the formation of human resources and the potential for realizing the nation's intelligence prosperity, and good character. There is quite a bit of da'wah that can be done through Islamic boarding schools, both da'wah which conveys Islamic teachings, as well as da'wah about life and of course for the formation of the character of the people.